The influence of isometric exercises of the quadriceps muscle on young female patients with anterior knee pain - Wilczyński, Jacek; Karolak, Przemysław; Karolak, Joanna (Medical Studies/Studia Medyczne, 2015)
Introduction: Anterior knee pain is a disease associated with abnormalities in the patellofemoral joint. It is a common reason for seeking advice from an orthopaedist. This problem is characterised by chronic pain in the anterior part of one or both knees. This issue often affects women, especially at a young age. The effect of this ailment is deterioration of the quality of life. This dysfunction significantly reduces abilities, and often prevents the performance of daily activities. Pain usually occurs during physical activity, but may also be accompanied by prolonged immobilisation of the knee joint. In defining the type of patellofemoral instability, orthopaedists use magnetic resonance imaging, arthroscopy, ultrasonography, and X-ray examination. A relatively effective method of treatment of pain in the patellofemoral joint is through isometric exercises of the quadriceps. They increase the strength of the quadriceps femoris muscle and reduce instability in the patellofemoral joint. Aim of the research: To evaluate the effectiveness of isometric exercises of the quadriceps muscle on young female patients with anterior knee pain. Material and methods : The study involved 30 women aged 13–44 years (mean age: 26.8 years), who had been diagnosed with pain in the front of the knee. Results and conclusions: Isometric exercises of the quadriceps muscle are an effective method of reducing anterior knee pain. Isometric exercises have a beneficial influence on improving physical activity, including performing basic activities of daily living. Student’s t distribution showed, that isometric exercises of the quadriceps muscle reduce pain at the front of the knee. Kruskal-Wallis test confirmed a significant reduction of anterior knee pain.